Portaria PRM Cachoeiro de Itapemirim/ES nº 4, de 30 de junho de 2021 - Paulo Henrique Camargos Trazzi (DMPF-e, Brasília, DF, 1º jul. 2021. Caderno Administrativo, p. 21., 2021)
Revoga a Portaria PRM Cachoeiro de Itapemirim/ES Nº 1/2021.